The Atrial Fibrillation and Oral anticoagulation/Antiplatelet agents Practices in Low Middle-Income settings - RWEYEMAMU, SAMWEL JACOB; Mutagaywa, Reuben; Majani, Naizihijwa; Waane, Tatizo; Kisenge, Peter Richard (European Journal of Applied Sciences, 2022)
Background: Atrial fibrillation (AF) is an arrhythmia which is diagnosed by the finding of irregularly irregular ventricular rhythm without discrete P waves in an electrocardiogram. Atrial fibrillation increases risk for intra-cardiac thrombosis and cerebral vascular event .it is a risk factor for ischemic stroke and affects abouts 33 million people globally and is more common in adults above 65 years. It a common complication among the patients with cardiovascular diseases. Aim of the study: The aim of this study was to audit the use oral anticoagulation/antiplatelet agents in patients with Atrial Fibrillation at Jakaya Kikwete Cardiac Institute Material and methods: A retrospective descriptive cross-sectional audit study which was conducted at Jakaya Kikwete cardiac institute among adult patients with a diagnosis atrial fibrillation. Patients were identified in a medpro systems and their age and sex were documented. Cross checking for the record of risk scores and OAC/antiplatelet prescription was done and recoded in a structured questionnaire which was designed to collect the data. Data analysis: The data entry and analysis were done using statistical package for social sciences (SPSS) version 20.0. Results Of 800 patients. 37(4.6%) were found to have a diagnosis of AF. Among patients with AF, females were 19 (51.4%), those aged 18-39 years were 13 (35.1%) same as those aged 40-64 years, 65+ years were 11 (29.7). Based on the structural/none structural diagnosis among patients with AF, 20 (54.0%) were having valvular heart diseases. and the rate of use of oral anticoagulation/antiplatelet agents was 73%. Among those using oral anticoagulation/antiplatelet agents, 24 (88.9%) were using warfarin, 2 (7.4%) NOAC and 1 (3.7%) was using antiplatelet (table 2). In terms of INR checking 24 (64.9%) were checked. Conclusion and Recommendations The rate of prescription of OAC were high while that for antiplatelet were low. The rate of INR checking in those who were using warfarin were high but not hundred percent. The documentation of risk scores before the prescription of OAC therapy was not done at all. We recommend for the good practice and follow the recommendations from ESC guideline 2020, our local protocol and evidence-based practice for the management of atrial fibrillation